Protein Intake, Nutritional Status, and Family Socioeconomic Relationships with Learning Achievement of Children Aged 13-15 Years at Nabil Husein Junior High School Samarinda Year 2022 - Jamil Anshory; Aulia Dwi Nur Anggraini; Satriani Satriani (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Nutritional problems in adolescents will affect the quality of human resources which can result in reduced generations and have an impact on the nation's economic situation in the future. Vulnerable aged 13-15 years experiencing nutritional needs much faster. Protein intake, nutritional status and socioeconomic status in several studies showed different results. The purpose of this study was to determine the relationship between protein intake, nutritional status, and socioeconomic status with the learning achievement of children aged 13-15 years at SMP Nabil Husein Samarinda. Quantitative research design, correlational descriptive type, cross sectional approach. The sample used was 49 students of class VIII using a purposive sampling technique. Protein intake was obtained through a 24-hour food recall interview, nutritional status measurements based on BMI/Age, and socioeconomic status were obtained by filling out a questionnaire form. The results obtained from this study were the relationship between protein intake and learning achievement with a p-value of 0.670, nutritional status with learning achievement with a p-value of 0.358, parents' education with learning achievement with a p-value of 0.429, parental income with learning achievement with a p-value -value 0.441, parents' work with learning achievement with a p-value of 0.437. The conclusion of this study is that there is no relationship between protein intake, nutritional status and socioeconomic status of parents with learning achievement of class VIII students of Junior High School Nabil Husein Samarinda.